PTH-123 Quality Of Life And Performance Status Scores Following Intestinal Transplantation Are Similar To Those Of Patients On Home Parenteral Nutrition In The Uk. (9th June 2014) - Pither, C; Duncan, S; Butler, A; Stroud, M; Smith, T; Calder, P; Rui, G; Chukualim, B; Woodward, J; Green, J; Charlotte, R; Sharkey, L; et al.
Abstract : Introduction: Survival following Intestinal transplantation (ITX) has improved, approaching that of home parenteral nutrition (HPN) at 5 years. We describe quality of life (QOL) and performance status (PS) on uncomplicated HPN, those with criteria for ITX due to complicated HPN (CHPN) and those after ITX. Methods: SF36 was used to assess QOL. Performance status was assessed by health related visual analogue scale (VAS), ECOG and Karnofsky performance score (KS). Results: [Table – grouped data]. There was a trend for QOL and PS to be lower on CHPN than HPN and ITX (not significant, NS) Paired data for SF36 pretransplant (CHPN) and post-transplant revealed "general health "was the only function to significantly improve (p < 0.05). Individual patients' total scores improved in 4/11 with a statistically significant improvement in a further in 3/11(p < 0.05) and were worse in 3/11. PS showed a trend for improvement post ITX compared to CHPN and HPN [All Wilcoxon signed rank, NS]. Conclusion: SF36 improves significantly in approximately 25%, but falls in 25% after ITX compared CHPN and trends suggest performance improvement after ITX. With more data effects of ITX on QOL and PS will emerge and if improvements are confirmed earlier transplantation for those dependent on HPN may be justifiable. Disclosure of Interest: None Declared.